UPAYA UNITED NATIONS EDUCATIONAL, SCIENTIFIC AND CULTURAL ORGANIZATION (UNESCO) DALAM MENJAGA KEBERADAAN MUSEUM SANGIRAN SEBAGAI WARISAN BUDAYA DUNIA TAHUN 2011-2016 - Juliana Harianja; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Cultural heritages are things from the past, which are valued by communities in recent time as part of their nation’s culture. In reality, among the community members there are problems that arise as a result of diverse perceptions, due to the fact that each perception is based on own interests as is the case with the Site of Sangiran. On the one hand, the Government, as part of the present community, has an idealistic orientation towards the Site of Sangiran as a cultural heritage which unquestionably needs to be protected for the purpose of scientific knowledge and national identity. The local people around Sangiran Site, on the other hand, consider it as their ancestors’ area which possesses valuable contents and advantages to improve their economic condition. This conflict and the consequences (fossil protection on the one hand and fossil trade on the other) have so far not been resolved. Meanwhile, the destruction of the Site of Sangiran as the World Cultural Heritage No. 593 is still continuing.The method of data collecting is done by collecting secunder data, then analyzed in qualitative to obtain the draft about the main problem by using deductive method. The method of this research is the method of qualitative descriptive. The data is obtained through secunder data such as, book, journal, magazine, newspaper and website.To prevent further damage, UNESCO as an international organization to perform its role and together with the Government of Indonesia signed Heritage Management Framework that formed in 2010-2013, established by UNESCO, Heritage Management Framework provides a variety of management strategies and policies that are effective in the protection of Sangiran Museum.Keywords: Sangiran Site, UNESCO, World Heritage